Игра в лапту: Рассказы / Василий Афонин - Афонин Василий Егорович (Сов. писатель, 1981)
Экземпляры: ф.7 (20181211) / Инвентарный номер: 1078 / Цена: 0.75 / Авт.знак: А94 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6